Cloning, expression, and purification of fusion antigens MPT83 and ESAT6 from the local strain of Mycobacterium tuberculosis in Escherichia coli as a seed vaccine candidate against tuberculosis - Rusdina Bte Ladju; Ahyar Ahmad; Abdul Karim; Rugaiyah Arfah; Rosana Agus; Najdah Hidayah; Muhammad Nasrum Massi; Astutiati Nurhasanah; Harningsih Karim; Irda Handayani (Journal of Advanced Biotechnology and Experimental Therapeutics)
Eradicating tuberculosis (TB) globally is increasingly challenging with the growing number of drug-resistant Mycobacterium tuberculosis (M. tuberculosis) strains. The development of more potent TB vaccines is critical to complement overall TB control strategies and overcome the growing challenge of drug resistance. In this study, the recombinant plasmid pGEM-T Easy- Rv2873 + Rv3875 has been generated by inserting the Rv3875 gene, which encodes the ESAT6 protein, into the pGEM-T Easy- Rv2873 vector at the BamHI/HindIII cloning site. Following transformation into E. coli JM109, the plasmid was extracted, PCR amplified, and DNA sequencing. The existence of the appropriate recombinant Rv2873 + Rv3875 fusion genes was confirmed through the observation of a band of 948 base pairs in the colony PCR product containing fusion antigens. A band measuring 3966 base pairs was observed in the recombinant plasmid pGEM-T Easy- Rv2873+Rv3875, supporting the presence of the desired fusion genes target. The fusion genes Rv2873+Rv3875 were cloned into the expression vector pTrcHisA. This resulted in the pTrcHisA Rv2873+Rv3875 recombinant fusion plasmid, which was subsequently introduced into the E. coli BL21 strain through transformation. The fusion protein, comprising the 6XHis tag, exhibited a molecular mass of around 28 kilo Dalton and was synthesized as an insoluble protein inside E. coli BL21. In conclusion, the purified recombinant fusion protein MPT83 and ESAT6 hold promise for TB diagnosis and show potential as vaccine candidates in the future. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 91-104]